Governança cooperativa: o papel da gestão de pessoas nas esferas decisórias em cooperativas de crédito - Santos, Vinícius Lóss dos (2023)
The central theme of this study is to establish the relationship between Cooperative Governance (GCoop) and People Management (PM), since PM is strategic in its relationship with the decision-making spheres in cooperative organizations. The literature shows that in various organizational segments, the PM area plays a fundamental role in the development of business strategies, as well as the development of strategic guidelines, through the development of people within the corporate world. And this development can occur through the application of PM policies and practices, which aim, in addition to supporting executive management, to also support the sphere of governance, in this case, cooperative governance, which is similar to corporate governance. However, here it brings together its differences, since it takes into account the elements of a cooperative organization, which is a society of people with a common interest. In this same sense, this study was directed towards credit cooperatives, which are located in a national financial environment, where they are subject to laws that establish governance policy, which makes it necessary to establish governance agents. In view of this, this study aims to understand the importance of including people management in the decision-making spheres of cooperative governance, in the context of credit unions. Within this proposal, the following specific objectives were outlined: a) to verify how people management relates to senior cooperative governance and management in the Credit Union under study; b) to identify the main challenges and advances in the interface between people management and cooperative governance in the case under study; c) to identify whether the relationship between people management and cooperative governance contributes to the qualification of decision-making on matters related to people strategy. Methodologically, this study is characterized as an applied social research, with a realistic approach, being developed at a descriptive level, in a qualitative methodological nature, and the technical procedure of the study consists of a case study. This study was carried out in cooperative organizations in the credit segment and the data were collected through semi-structured interviews, focus groups and on-site observation. The information was organized in tables and charts, and then analyzed descriptively, and was carried out in group associations. The data were then organized using dynamic tables, and then weighted and triangulated using content analysis. The results point to the role and importance of the people management area, supporting the sphere of governance within cooperatives, with the support of people management policies and practices, associated with cooperative governance policies and practices, where it can play an influential and engaging role to effectively support decision-making. It is concluded that the people management relationship with all governance agents is of fundamental importance, because the closer and more aligned GP and GCoop are, the greater and more effective the contributions to senior leadership will be, thus obtaining better results that can be reflected in the organizational strategies of cooperatives, having repercussions on employee engagement actions with members and communities.